2020
DOI: 10.1155/2020/1624632
|View full text |Cite
|
Sign up to set email alerts
|

Rotational Stability of a New Posterior Chamber Toric Phakic Intraocular Lens

Abstract: Purpose. To evaluate the refractive results and rotational stability of Eyecryl toric phakic intraocular lens (pIOL). Methods. In this retrospective single-surgeon case series, manifest refraction, visual acuities, endothelial cell density (ECD), and pIOL rotation were evaluated over 6 months. Results. 43 eyes from 23 patients were included. At 6 months, the SE was within ±0.50  D of emmetropia in 30 (70%) eyes and within ±1.00  D of emmetropia in 39 (91%) eyes. The efficacy and safety indices were 1.25 ± 0.38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
1
6
0
3
Order By: Relevance
“…Критерии включения: в соответствии с существующими рекомендациями [8][9][10]: миопия выше -9,0 D (до -25,0 D); миопия выше -3,0 D при наличии противопоказаний к эксимерлазерной коррекции; гиперметропия более +6,0 D (до 16,0 D); астигматизм до 6,0 D; глубина передней камеры глаза (ACDendo) при использовании переднекамерных линз не менее 3,0 мм, при использовании заднекамерных линз не менее 2,8 мм; плотность эндотелиальных клеток роговицы не менее 2000 клеток/мм 2…”
Section: материал и методыunclassified
See 2 more Smart Citations
“…Критерии включения: в соответствии с существующими рекомендациями [8][9][10]: миопия выше -9,0 D (до -25,0 D); миопия выше -3,0 D при наличии противопоказаний к эксимерлазерной коррекции; гиперметропия более +6,0 D (до 16,0 D); астигматизм до 6,0 D; глубина передней камеры глаза (ACDendo) при использовании переднекамерных линз не менее 3,0 мм, при использовании заднекамерных линз не менее 2,8 мм; плотность эндотелиальных клеток роговицы не менее 2000 клеток/мм 2…”
Section: материал и методыunclassified
“…Плотность эндотелиальных клеток в нашем исследовании через 3 года после операции уменьшилась в среднем на 0,09%. По данным ряда авторов, этот показатель уменьшается в среднем на 4-5% [4,7,9,16,21].…”
Section: оригинальные статьи обсуждениеunclassified
See 1 more Smart Citation
“…Although a limited number of previous studies have reported the refractive predictability and safety of the Eyecryl PC pIOL, the mean follow-up in the longest series was 3 years. [9][10][11][12][13][14][15] The goal of the study was to assess the long-term efficacy and safety of Eyecryl posterior chamber spherical pIOL implantation in individuals with high myopia.…”
mentioning
confidence: 99%
“…Numerous manufacturers have introduced economically viable, biocompatible alternatives such as hydrophilic acrylic-based foldable PIOLs such as implantable phakic contact lens (IPCL; Care Group, India), Eyecryl PIOL (Biotech Vision Care, Ahmedabad, India), and refractive implantable lens (RIL; Appasamy, Chennai, India). 2,[6][7][8][9] A couple of studies report good outcome in correcting refractive error with these hydrophilic acrylic implants. 8,9 The RIL has a meniscus design with an overall size of 11.5 to 13.25 mm and an optic size of 4.5 to 5.8 mm and provides a treatment range from +10 to 224 diopter (D).…”
mentioning
confidence: 99%